Diseño de un plan de comunicación integral para una empresa de servicios petroleros - Díaz García, Sonia Carolina (2015)
This research addresses the interesting world of organizational communication. To this end, it has worked with oil services company, whose name has not been evidenced by respecting the confidentiality agreement was signed with the institution to perform this study. The research consists of three chapters; in the first chapter a theoretical approach to organizational communication is made from the perspective of several authors; however it is taken as central to author Joan Costa who has made significant contributions to this field. It has also considered the analysis and study of new technologies (ICTs) as tools necessary for business competitiveness. In the second chapter, the internal and external diagnosis made by the techniques of field observation and survey results to further evidence obtained by graphic exposed. In the third chapter, a brief introduction of the state of the company and its organizational guidelines is to give way to comprehensive communication plan intends to implement in the same, which includes strategies that seek to consolidate the firm in the market ; as well as its internal and external development under FODA OPRI scheme. Finally, we seal on this work with conclusions and recommendations prepared according to the research experience has been obtained throughout the study and a perspective of human, social and personal development that will go alongside the growth of the organization.